TLR3 and TLR7 modulate IgE production in antigen induced pulmonary inflammation via influencing IL-4 expression in immune organs. - Liesu Meng; Xiaojing He; Wenhua Zhu; Xudong Yang; Congshan Jiang; Qingzhu Sun; M B; Simeng Zhang; Qian Xue; Xinfang Xie; Shemin Lu; Shemin Lu (PLoS ONE, 2011)
Background Toll-like receptors (TLRs) as pattern recognition receptors, participate in both innate and adaptive immune responses, and seem to play an important role in the pathogenesis of asthma. This study aimed to identify key TLRs involved in antigen induced pulmonary inflammation (AIPI), a rat model for asthma, and to explore the role of TLRs in the disease development. Methods and findings E3 rats were sensitized with ovalbumin (OVA)/alum intraperitoneally and intranasally challenged with OVA to induce AIPI model. TLR1-9 and cytokine mRNA expression in spleen, lung and mediastinal lymph node (mLN) tissues were screened by quantitative real-time polymerase chain reaction. TLR7 expression was found to be significantly down-regulated in spleen while TLR3 and TLR8 expression was up-regulated in mLN of AIPI rats. Furthermore, imiquimod (a ligand of TLR7) and TLR3 specific short-hairpin RNA plasmid for RNA interference were administrated, respectively, in vivo to AIPI rats to observe their effects on the disease by assessing various asthmatic parameters. The numbers of total cells, eosinophils, macrophages and lymphocytes were counted according to differential morphology in bronchoalveolar lavage fluid. Serum IgE and OVA specific IgG(1) concentration was detected by enzyme-linked immunosorbent assay. The results showed that both TLR7 ligand treatment and TLR3 RNAi in vivo decreased serum IgE level and interleukin-4 mRNA expression. Conclusion/significance TLR3 in mLN and TLR7 in spleen both systemically modulate disease development in AIPI rats via altering serum IgE concentration relevant to Th2 responses. And these findings may provide an important clue for further research in the asthma pathogenesis and suggest a new remedy for asthma treatment.